Information Technologies and Analytics as Decision Support Systems in Hospital Logistics: Four Research Experiences in the Colombian Case - Ospina, Victoria Eugenia; Cardona, Andrés Felipe; Guerrero, William (Colombia., 2017)
This article presents four research experiences in hospital logistics using simultaneously mathematical models and information management. The cases analyzed included the efficient scheduling of nursing shifts, kidney exchange programs, the design of medical equipment maintenance policies, and the design of rapid response tools for cardiovascular accidents. The problems found are presented and the technological solutions developed are described. The results obtained show the importance of combining information management and optimization models in the four cases in question. Future work includes the collection of historical data to fine-tune and improve the performance of the solutions developed, and as such to predict the behavior of the logistics systems studied.

Este artículo presenta cuatro experiencias de investigación en logística hospitalaria utilizando simultáneamente modelos matemáticos y gestión de la información. Los casos analizados incluyeron la programación eficiente de los turnos de enfermería, los programas de intercambio renal, el diseño de políticas de mantenimiento de equipos médicos y el diseño de herramientas de respuesta rápida para accidentes cardiovasculares. Se presentan los problemas encontrados y se describen las soluciones tecnológicas desarrolladas. Los resultados obtenidos muestran la importancia de combinar modelos de gestión y optimización de la información en los cuatro casos en cuestión. El trabajo futuro incluye la recopilación de datos históricos para afinar y mejorar el rendimiento de las soluciones desarrolladas y, como tal, predecir el comportamiento de los sistemas logísticos estudiados.
Keywords: Cuidado de la salud; Analítica; Logística hospitalaria; Conocimiento administrativo; Sistemas logísticos; Modelos matemáticos; IoT; healthcare; analytics; hospital logistics; knowledge management; optimization